Influence of the micromycete Fusarium culmorum and its antagonists on the state of the antioxidant system of Melissa officinalis L. - Svetlana Skugoreva; Polina Gushchina; Yana Sharipova; Larisa Darovskikh (Chimica Techno Acta)
In recent years, the popularity of herbal medicine has increased. Lemon balm (Melissa officinalis L.) is a perennial essential oil herb that has been used as a medicinal plant for more than 2 thousand years. It is known that the productivity of plants is directly related to their resistance to phytopathogens, in particular, micromycetes of the genus Fusarium. One of the main mechanisms of plant damage by phytopathogens is oxidative stress. Micromycetes of the genus Trichoderma and soil cyanobacteria (CB) occupy an important place among the natural antagonists of fungi of the genus Fusarium. The aim of the work was to study the state of the antioxidant system of Melissa officinalis L. plants when grown on substrates contaminated with the micromycete Fusarium culmorum and its antagonists – the cyanobacterium Fischerella muscicola and the micromycete Trichodеrma viride. It was found that the presence of the pathogenic micromycete F. culmorum in the soils for growing lemon balm for two months has a stressful effect on lemon balm plants: the intensity of lipid peroxidation, the content of phenolic compounds and the amount of antioxidants in the in plant leaves were significantly higher than in the control. At the same time, at elevated temperatures, the content of phenolic compounds increased, which may be due to increased metabolism and the level of oxidative stress. The introduction of microorganisms-antagonists F. muscicole and T. viride into the soil makes it possible to activate the work of the antioxidant system of plants and reduce the effects of oxidative stress almost to the level of control. The studied antagonists can be recommended as promising for the development of biological products on their basis in order to protect medicinal plants from fusarium diseases.